The Influence of Company Internal and External Factors on Audit Delay (Empirical Study on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange 2016-2020) - Susanto, Evelin Vincent; Ulum, Akhmad Samsul; Ardianingsih, Arum (Budapest International Research and Critics University, 2021)
This study aims to examine the effect of the company's internal and external factors on audit delay. Internal factors include profitability, financial debt, audit effort, and the size of the board of commissioners, while external factors include audit opinion. The data used is the publication of the financial statements of companies listed on the Indonesia Stock Exchange (IDX) from manufacturing companies in the consumer goods industry sector from 2016 to 2020. The sampling technique used is purposive sampling and obtained 27 companies for 5 consecutive years, while the sampling technique used was purposive sampling. The analysis used is multiple linear regression analysis. Based on the results of this study, there are 2 variables that have a negative effect on audit delay, namely audit effort and the size of the board of commissioners. Meanwhile, audit opinion, profitability and financial debt have no effect on audit delay.